Comparative study of physical properties of hybrid and UV offset inks - Jašúrek, Bohumil; Odstrčilová, Helena; Vališ, Jan (University of Pardubice, 2013)
Hybrid inks represent a type of inks that are cured by two various mechanisms, oxypolymerization and polymerization induced by UV radiation. The printability of offset inks strongly depends on the rheological properties of printing inks, their tack and fountain solution pick-up behaviour. In this work, two process hybrid inks and two UV curable inks were tested. The studied process inks were in both cases cyan and magenta. The tested physical properties were evaluated for unemulsified inks and their emulsions with fountain solution. The emulsions of inks and fountain solution were characterised by the amount and rate of fountain solution pick-up. The rheological properties (flow behaviour, thixotrophy, and viscosity relaxation) were measured with rotational rheometer RV1 HAAKE, the tack and misting with Tackmaster-92.